Control of Body Weight by Eating Behavior in Children - Zandian, Modjtaba; Bergh, Cecilia; Ioakimidis, Ioannis; Esfandiari, Maryam; Shield, Julian; Lightman, Stafford; Leon, Michael; Södersten, Per (Frontiers in Pediatrics, 2015)
Diet, exercise, and pharmacological interventions have limited effects in counteracting the worldwide increase in pediatric body weight. Moreover, the promise that individualized drug design will work to induce weight loss appears to be exaggerated. We suggest that the reason for this limited success is that the cause of obesity has been misunderstood. Body weight is mainly under external control; our brain permits us to eat under most circumstances, and unless the financial or physical cost of food is high, eating and body weight increase by default. When energy-rich, inexpensive foods are continually available, people need external support to maintain a healthy body weight. Weight loss can thereby be achieved by continuous feedback on how much and how fast to eat on a computer screen.